Pregnancy dietary cholesterol intake, major dietary cholesterol sources, and the risk of gestational diabetes mellitus: A prospective cohort study. Issue 5 (May 2020) - Wu, Yuanjue; Sun, Guoqiang; Zhou, Xuezhen; Zhong, Chunrong; Chen, Renjuan; Xiong, Ting; Li, Qian; Yi, Nianhua; Xiong, Guoping; Hao, Liping; Yang, Nianhong; Yang, Xuefeng
Summary: Background & aims: The Scientific Report of 2015 Dietary Guidelines Advisory Committee recommended the elimination of dietary cholesterol limits. However, cholesterol intake increases during pregnancy and studies regarding the association between dietary cholesterol and gestational diabetes mellitus (GDM) are limited. We evaluate the association of total dietary cholesterol and different sources of cholesterol intake during pregnancy, with GDM risk and blood glucose levels in a Chinese prospective cohort study. Methods: A total of 2124 pregnant women from the Tongji Maternal and Child Health Cohort was included. A validated semi-quantitative food frequency questionnaire was used to assess dietary cholesterol intake prior to GDM diagnosis. GDM was diagnosed by the 75-g 2-h oral glucose tolerance test. Cubic-restricted spline function and logistic regression analyses were used to evaluate the association between dietary cholesterol intake during pregnancy and GDM. Generalized linear models were conducted to examine the associations of cholesterol intake with fasting blood glucose (FBG), 1-h post-load blood glucose (PBG) and 2-h PBG. Results: The average dietary cholesterol intake was 379.1 mg/d, and cholesterol from eggs explained 64.2% of the variability. Total dietary cholesterol intake and cholesterol from eggs rather than other foods, were linearly associated with GDM risk, with adjusted OR for GDM of 2.10 (95% CI : 1.24, 3.58) for total cholesterol intake and 1.83 (95% CI : 1.08, 3.07) for cholesterol from eggs comparing the highest versus lowest quintile. A 100-mg/d increase in total cholesterol and cholesterol from eggs intake were associated with an increased GDM risk by 18% and 16%, respectively. Moreover, higher maternal dietary total cholesterol could increase FBG and 1-h PBG, while cholesterol from eggs increased FBG only. Conclusion: Higher dietary cholesterol from eggs intake during pregnancy was associated with greater risk of GDM. Highlights: High dietary cholesterol intake increased gestational diabetes mellitus risk. Cholesterol from eggs, not others food, increased gestational diabetes mellitus risk. High dietary cholesterol intake increased fasting and 1 h post-load blood glucose. Cholesterol from eggs intake increased fasting but not post-load blood glucose.